2018
DOI: 10.7150/jca.25967
|View full text |Cite
|
Sign up to set email alerts
|

CDK5 Functions as a Tumor Promoter in Human Lung Cancer

Abstract: Cyclin-dependent kinase 5 (CDK5), an atypical member of the cyclin-dependent kinase family, plays an important role in the nervous system. Recent studies have shown that CDK5 is also associated with tumors. However, few studies have been done to investigate the mechanism underlying the connection between CDK5 and cancers. To explore the role of CDK5 in cancers by using an extensive bioinformatics data mining process. We mined the transcriptional, survival, functions and structure of CDK5 gene through databases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 69 publications
1
27
0
Order By: Relevance
“…Given that CDK5 is activated and overproduced in lung cancer, 25,26 we speculated that it might play an oncogenic role in lung cancer. To test this hypothesis, we knocked down the expression of CDK5 and found that all 3 SiRNAs and 2 ShRNAs efficiently knocked down CDK5 at the protein level (Fig.…”
Section: Cdk5 Knockdown Suppresses Lung Cancer Progression In Vitro Amentioning
confidence: 99%
See 1 more Smart Citation
“…Given that CDK5 is activated and overproduced in lung cancer, 25,26 we speculated that it might play an oncogenic role in lung cancer. To test this hypothesis, we knocked down the expression of CDK5 and found that all 3 SiRNAs and 2 ShRNAs efficiently knocked down CDK5 at the protein level (Fig.…”
Section: Cdk5 Knockdown Suppresses Lung Cancer Progression In Vitro Amentioning
confidence: 99%
“…)))P < .001 (n Z 3). Scale bar,25 mm. (E) A549 and H1299 cells transfected with the indicated plasmids and siRNAs were exposed to the indicated radiation doses.…”
mentioning
confidence: 99%
“…CDK5 regulates cell cycle progression, cellular proliferation, and cell migration, and therefore, dysregulation of CDK5 in cellular functions can cause oncogenesis leading to lung and colorectal cancer [46,47]. Notably, when the cancer cells were treated with inhibitors of PPARĪ³ phosphorylation, the cancer cells showed more susceptibility to anti-cancer agents inducing DNA damage responses [53].…”
Section: Discussionmentioning
confidence: 99%
“…To compare the adiponectin production-enhancing activity of CDK5 inhibitors, hBM-MSCs were co-treated with butyrolactone I, Ro-3306, A-674563, AT7519, or roscovitine with IDX when adipogenesis was induced (Figure 2). Because CDK5 inhibitors are cytotoxic or apoptotic against diverse normal or cancer cell lines [46,47], the non-cytotoxic concentrations of Ro-3306, A-674563, AT7519, and roscovitine were chosen for screening their adiponectin production-enhancing activity (Figure 2A). As compared to that of the IDX control, butyrolactone I and roscovitine significantly enhanced adiponectin production, whereas the other CDK5 inhibitors Ro-3306, A-674563, and AT7519 exhibited no significant effects on adiponectin production in hBM-MSCs at non-cytotoxic concentrations (Figure 2A).…”
Section: The Adiponectin Production-enhancing Activity Of Butyrolactomentioning
confidence: 99%
“…It is believed that CDK5 promotes self-renewal of malignant brain tumor stem cells such as glioma stem cells [54]. Bioinformatic analyses have demonstrated that increased CDK5 expression importantly supports the migration, proliferation, and metastasis of human lung cancer [55]. One study demonstrated that CDK5 promotes DNA replication due to stress checkpoints, and therefore contributes to the metastasis of breast cancer [41].…”
Section: Cdk5 and Prostate Cancermentioning
confidence: 99%